2016
DOI: 10.1016/j.visres.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Caledonian face test: A new test of face discrimination

Abstract: This study aimed to develop a clinical test of face perception which is applicable to a wide range of patients and can capture normal variability. The Caledonian face test utilises synthetic faces which combine simplicity with sufficient realism to permit individual identification. Face discrimination thresholds (i.e. minimum difference between faces required for accurate discrimination) were determined in an "odd-one-out" task. The difference between faces was controlled by an adaptive QUEST procedure. A broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 67 publications
5
40
0
Order By: Relevance
“…This value is in line with results of previous investigations of synthetic face discrimination (Loffler et al, 2005a, Wilson, Loffler & Wilkinson, 2002. For example, Logan et al (2016) reported a range between 3.33 and 8.84% for 52 typical observers.…”
Section: Full Facessupporting
confidence: 92%
See 3 more Smart Citations
“…This value is in line with results of previous investigations of synthetic face discrimination (Loffler et al, 2005a, Wilson, Loffler & Wilkinson, 2002. For example, Logan et al (2016) reported a range between 3.33 and 8.84% for 52 typical observers.…”
Section: Full Facessupporting
confidence: 92%
“…Thirdly, a comparable BOLD fMRI signal in the FFA for face photographs and synthetic faces suggests that the brain processes both stimuli in a similar way (Loffler et al, 2005b). Finally, two recent studies (Lee et al, 2010, Logan et al, 2016 identified impairments of synthetic face discrimination in patients with developmental prosopagnosia. In one of them, synthetic faces were employed within a new test of face discrimination (the Caledonian face test; Logan et al 2016).…”
Section: Do Synthetic Faces Engage Normal Face Processing Mechanisms?mentioning
confidence: 90%
See 2 more Smart Citations
“…A"perceptual" version of this test, the Cambridge Face Perception Test (CFPT, Duchaine, Germine & Nakayama, 2007), much less widely used, is also associated with a large interindividual variability in performance (Bowles et al, 2009;Duchaine et al, 2007;Garrido, Duchaine, & Nakayama, 2008). However, the CFPT is not based on matching of different individual faces, but rather involves similarity judgments on morphed faces (see also Logan, Wilkinson, Wilson, Gordon, & Loffler, 2016), i.e. a task which is also likely to be highly influenced by higher-level cognitive processes.…”
Section: Computerized Benton Facial Recognition Testmentioning
confidence: 99%